Tumbuhan Peneduh Di Wisata Wadu Jao Sebagai Nilai Konservasi Di Kabupaten Dompu - Oktavianus Sarno; Nikman Azmin; Nurul Fahida; Hartati (JUSTER : Jurnal Sains dan Terapan, 2024)
This research aims to describe the types of plants found on the Wadu Jao Coast, Dompu Regency, West Nusa Tenggara and the use of plant types as learning media. This research was carried out around Wadu Jao Tourism. The method used is an exploratory survey method by means of observation which includes identifying plant types by combing several locations which are used as sampling points for plants which are considered to be criteria for shade plants by observing the structure of tree leaves, stems and branches. In this research, 14 types of shade plants were found consisting of 10 families.